MTUN tasked with finding ways to boost TVET will be 13th Malaysia Plan priority - T.N., Alagesh (New Straits Times Press (M) Bhd., 2023)
PEKAN: Universities under the Malaysian Technical University Network (MTUN) have been instructed to look into measures toboost student enrolment and programmes to meet the country's growing demands for technical and vocational education and training (TVET).